From Undergraduates to Doctorates: Exploring Student Perceptions of Effective Management Practices for Success - Khoirun Nisa; Munirul Abidin (STAI Terpadu Yogyakarta, 2024)
This study aims to investigate and analyze success management patterns based on the perceptions of students from different levels of education: undergraduate, master's, and doctoral. The main focus of this study is to understand how students at each level of education interpret, apply, and modify success management strategies according to academic and professional needs. The research method used in this study is a descriptive phenomenological approach with a qualitative approach. Success management based on the research results is classified into steps in achieving success, self-motivation, and the intended product of success. The steps to success consist of time management, setting targets, adding relationships, trying, praying, and opportunities that meet efforts. Self-motivation plays an important role in success management. Self-motivation can come from oneself or from external factors such as family, finances, and usefulness to others. The product of success, or the definition of success, can be in the form of achievement or accomplishment.